Earthworms (Lumbricidae) and Leches (Hirudinea) from neighbouring mountains Galichica and Petrino - Sapkarev, Jonče (Macedonian Journal of Ecology and Environment, 2001)
In this paper the results of the investigations on the structure of two annelid groups, earthworms and leeches, from the mountain massif Galichica and Petrino are presented. Besides the qualitative composition of these two animal groups, their quantitative relations from various habitats and for the lumbricids of various forest soils also, were explored.